2017
DOI: 10.2174/1566523217666170510160527
|View full text |Cite
|
Sign up to set email alerts
|

Delivering siRNA with Dendrimers: In Vivo Applications

Abstract: Over the last decades, gene therapy has emerged as a pioneering therapeutic approach to treat or prevent several diseases. Among the explored strategies, the short-term silencing of protein coding genes mediated by siRNAs has a good therapeutic potential in a clinical setting. However, the widespread use of siRNA will require the development of clinically suitable, safe and effective vehicles with the ability to complex and deliver siRNA into target cells with minimal toxicity. Lately, dendrimers have gained c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 143 publications
(192 reference statements)
0
10
0
Order By: Relevance
“…Dendriplexes prepared on the basis of siRNA and PAMAM or carbosilane dendrimers were of similar size [4,30,41]. The uptake of such large complexes can be difficult [41], but it has been demonstrated that PAMAM, carbosilane and phosphorus dendrimers can efficiently deliver siRNAs into the cells [5,19,20]. Small particles are taken up by clathrindependent endocytosis, whereas particles > 500 nm, such as dendriplexes, are taken up by cells by caveolae [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendriplexes prepared on the basis of siRNA and PAMAM or carbosilane dendrimers were of similar size [4,30,41]. The uptake of such large complexes can be difficult [41], but it has been demonstrated that PAMAM, carbosilane and phosphorus dendrimers can efficiently deliver siRNAs into the cells [5,19,20]. Small particles are taken up by clathrindependent endocytosis, whereas particles > 500 nm, such as dendriplexes, are taken up by cells by caveolae [42].…”
Section: Discussionmentioning
confidence: 99%
“…Different types of dendrimers can have quite different properties; for instance, cationic carbosilane dendrimers (CBS) have been used as non-viral carriers delivering human immunodeficiency virus (HIV)-peptides into dendritic cells [7], whereas amine-terminated poly-(amidoamine) PAMAM dendrimers were applied as a complex to deliver siRNAs to lung alveolar epithelial A549 cells, resulting in genes silencing [6] PAMAM dendrimers were applied to create complexes with siRNAs and deliver it to lung alveolar epithelial A549 cells, resulting in genes silencing. There is much evidence that nucleic acid form complexes with phosphorus, carbosilane, and PAMAM dendrimers, with increasing transfection efficiency of DNA and RNA into cells [5,19,20]. Current attempts to modify the dendrimers for greater efficiency have been undertaken; Hashemi et al 2016 [15] indicated that heterocyclic amine-modified poly-(amidoamine) and poly-(propylenimine) dendrimers facilitate gene delivery to neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their tunable chemical structure, dendrimers have shown many advantages, such as their high solubility in different media, hydrophobic or hydrophilic cavities in the interior, high biocompatibility, and low immunogenicity [73,76,79,80]. Related to this, and also due to their attractive chemical and physical characteristics, several applications have been presented in the biomedical and materials fields [73,77,79,81].…”
Section: Dendrimer-based Nanosystemsmentioning
confidence: 99%
“…Through these strategies, the bioavailability and protection of the different carried cargos is increased, enhancing the likelihood of reaching the target tissue or cells. These features and versatility for drug transport have made these promising nanomaterials to be explored as vectors for both gene and drug delivery [ [10], [11], [12], [13], [14]]. Additionally, dendrimers present further improved intrinsic structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The generation (G) of PAMAM dendrimers also affects biocompatibility. Increasing G increases their multivalency, but it is also known to increase toxicity [6,10,20]. Therefore, a compromise between the highest possible G and the least toxicity exerted in contact with cells should be reached.…”
Section: Introductionmentioning
confidence: 99%